Roles and Clinical Applications of OPG and TRAIL as Biomarkers in Cardiovascular Disease. (21st April 2016) - Bernardi, Stella; Bossi, Fleur; Toffoli, Barbara; Fabris, Bruno
Abstract : Cardiovascular diseases (CVD) remain the major cause of death and premature disability in Western societies. Assessing the risk of CVD is an important aspect in clinical decision-making. Among the growing number of molecules that are studied for their potential utility as CVD biomarkers, a lot of attention has been focused on osteoprotegerin (OPG) and its ligands, which are receptor activator of nuclear factor κ B ligand (RANKL) and TNF-related apoptosis-inducing ligand. Based on the existing literature and on our experience in this field, here we review what the possible roles of OPG and TRAIL in CVD are and their potential utility as CVD biomarkers.